Effectiveness of Reality Therapy Intervention on Reducing Depression and Anxiety of Mothers with Children with Special Needs - Gholami, Saghar; Massoumi, Ahmad (Iranian Journal of Neurodevelopmental Disorders, 2023)
Background and Purpose: Depression and Anxiety are among the most important psychological disorders entangling a wide range of individuals. The purpose of this research is to determine the effectiveness of Reality Therapy on reducing depression and anxiety of mothers with children with special needs who have been a patient at Parand city clinic in 2021.Method: The current research was a semi-experimental type with a pretest-posttest control group design. The statistical population of the research includes all mothers with children with special needs in Parand city, of which 30 were selected by convenience sampling method and randomly divided into two experimental and control groups (15 in each group). The participants initially took the Beck’s Questionnaire (1996), Goldberg's General Health Questionnaire (1979), and the Spielberger’s Anxiety Questionnaire (1971). Subsequently, the Reality Therapy package was implemented for the experimental group whereas the control group did not receive any training. Finally, both experimental and control groups were reevaluated. Results were analyzed by SPSS24 and through univariate analysis of variance.Results: The results showed that Reality Therapy can in fact reduce depression and anxiety of mothers with children with special needs (p> 0/05).Conclusion: Based on the results, it is concluded that Reality Therapy can be implied for mothers with children with special needs to decrease their depression and anxiety